2015
DOI: 10.1098/rspb.2014.2881
|View full text |Cite
|
Sign up to set email alerts
|

Composition of symbiotic bacteria predicts survival in Panamanian golden frogs infected with a lethal fungus

Abstract: Symbiotic microbes can dramatically impact host health and fitness, and recent research in a diversity of systems suggests that different symbiont community structures may result in distinct outcomes for the host. In amphibians, some symbiotic skin bacteria produce metabolites that inhibit the growth of Batrachochytrium dendrobatidis (Bd), a cutaneous fungal pathogen that has caused many amphibian population declines and extinctions. Treatment with beneficial bacteria (probiotics) prevents Bd infection in some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
156
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(160 citation statements)
references
References 66 publications
2
156
0
Order By: Relevance
“…In amphibians, several studies that have tried to treat adult amphibians with single or mixed probiotics have failed to see establishment of the bacteria, presumably due to competition with the resident microbes and/or host filtering (56)(57)(58). The same is true in human studies, although treatments with more complex mixtures of probiotics (e.g., fecal transplants) are often more successful (55).…”
Section: Discussionmentioning
confidence: 80%
“…In amphibians, several studies that have tried to treat adult amphibians with single or mixed probiotics have failed to see establishment of the bacteria, presumably due to competition with the resident microbes and/or host filtering (56)(57)(58). The same is true in human studies, although treatments with more complex mixtures of probiotics (e.g., fecal transplants) are often more successful (55).…”
Section: Discussionmentioning
confidence: 80%
“…This paper should be read in conjunction with two others that show how the Panamanian frogs which had experienced a lethal fungal infection, have now overcome the infection via commensal microbes. 64,65 What was not mentioned however, is that these vertebrates contain toxins that almost certainly are adsorbed from their diet of specific ants.…”
Section: Insect-microbe Symbiosesmentioning
confidence: 99%
“…Given the potential importance of symbiotic cutaneous bacteria in innate immune defence against Bd infection (Harris et al 2009) Understanding that these species likely slough infrequently may help pinpoint when to best bioaugment their skin with beneficial anti-Bd bacteria (Becker et al 2011, Becker et al 2015, as addition of the bacteria immediately after sloughing may allow for colonisation when resident bacterial populations are low ).…”
Section: Discussionmentioning
confidence: 99%
“…Sloughing may also benefit the pathogen by revealing newly keratinised epidermis free of cutaneous symbiotic bacteria. It has been demonstrated that some symbiotic microbes on the skin of amphibians can prevent morbidity associated with Bd infection (Harris et al 2009;Becker & Harris 2010;Becker et al 2015), thus, sloughing may actually increase susceptibility of the epidermis to invading pathogens.…”
Section: Skin Sloughing: Both Immune Defence and Sign Of Disease?mentioning
confidence: 99%
See 1 more Smart Citation